2012
DOI: 10.1002/ptr.4898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Astaxanthin Supplementation on Paraoxonase 1 Activities and Oxidative Stress Status in Young Soccer Players

Abstract: The purpose of the study was to examine the effects of astaxanthin (Asx) on paraoxonase (PON1) activities and oxidative stress status in soccer players. Forty soccer players were randomly assigned in a double-blind fashion to Asx and placebo (P) group. Blood samples were obtained before, 45 and 90 days after supplementation. PON1 activity was assessed by using two substrates: paraoxon and diazoxon. The oxidative stress biomarkers were also examined: total sulphydryl group content (-SH groups), thiobarbituric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…PON1 is a hepatic enzyme which prevents and/or delays the oxidation of LDL [ 33 ]. Thus, the prevention of plasma lipid peroxidation in humans due to astaxanthin, as reported by Barlic and co-workers [ 34 ], may be partly mediated by an induction of paraoxonase-1. Recently, it has been shown that PON1 also counteracts oxidative stress induced by mercury chloride, thereby offering a beneficial strategy against HgCl 2 toxicity [ 35 ] which may be of particular interest for fish nutrition.…”
Section: Resultsmentioning
confidence: 78%
“…PON1 is a hepatic enzyme which prevents and/or delays the oxidation of LDL [ 33 ]. Thus, the prevention of plasma lipid peroxidation in humans due to astaxanthin, as reported by Barlic and co-workers [ 34 ], may be partly mediated by an induction of paraoxonase-1. Recently, it has been shown that PON1 also counteracts oxidative stress induced by mercury chloride, thereby offering a beneficial strategy against HgCl 2 toxicity [ 35 ] which may be of particular interest for fish nutrition.…”
Section: Resultsmentioning
confidence: 78%
“…( 95 ) Although some clinical studies have shown that intake of astaxanthin improves biomarkers of systemic oxidative stress, the effects on GI diseases have not been extensively studied. ( 96 , 97 ) However, a recent clinical trial has demonstrated that higher dose of astaxanthin, 40 mg/day, reduced reflux symptoms in patients with gastroesophageal reflux disease (GERD), but had no curative effects on functional dyspepsia. ( 98 ) Further studies are required regarding the clinical efficacy of astaxanthin to treat oxidative stress-induced GI disorders.…”
Section: Natural and Synthetic Chemical Compounds That Enhance Nrf2-dmentioning
confidence: 99%
“…It was reported that regular physical activity might increase PON1 activity [ 26 ]. Astaxanthin supplementation (4 mg/day) for 90 days showed a beneficial effect in improving PON1 activity as well as the total sulphydryl group content in young soccer players [ 27 ]. The same researchers also reported that post-exercise creatine kinase (CK) and aspartate aminotransferase (AST) levels were significantly lower in their astaxanthin group compared to a placebo group [ 28 ].…”
Section: Multiple Anti-atherosclerotic Effects Of Astaxanthinmentioning
confidence: 99%